Clozapine-induced antineutrophil cytoplasmic antibody-associated vasculitis: a case report. (2nd January 2020) - Fujimoto, Sho; Ueda, Naoyasu; Nishimura, Naoya; Naito, Atsushi; Hiura, Junki; Mashiba, Kouichi; Ikai, Ayane; Marutsuka, Kousuke; Mizuno, Kentaro
Abstract: Clozapine is the most effective antipsychotic medication for refractory schizophrenia, but it has many possible serious side effects, including antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). However, the rare case reports available have not presented sufficient characteristic features of drug-induced AAV. Herein, we report a case of a 48-year-old Japanese woman with schizophrenia who presented with fever, arthralgia, myalgia and skin rash after 2 years of clozapine treatment. Her C-reactive protein (CRP) level increased, myeloperoxidase ANCA was positive and skin biopsy revealed leukocytoclastic vasculitis. Initially, steroid administration achieved remission, but her symptoms and high CRP levels relapsed every time the steroid dosage was tapered down. Upon discontinuation of clozapine, her symptoms and elevated CRP level immediately improved and the steroid was successfully tapered and discontinued. This outcome suggested that clozapine was the main cause of AAV.